2017
DOI: 10.1371/journal.pgen.1006554
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Dosage Compensation Buffers Genetic Perturbations to Stoichiometry of Protein Complexes

Abstract: Understanding buffering mechanisms for various perturbations is essential for understanding robustness in cellular systems. Protein-level dosage compensation, which arises when changes in gene copy number do not translate linearly into protein level, is one mechanism for buffering against genetic perturbations. Here, we present an approach to identify genes with dosage compensation by increasing the copy number of individual genes using the genetic tug-of-war technique. Our screen of chromosome I suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(101 citation statements)
references
References 63 publications
4
97
0
Order By: Relevance
“…It has been the basis of ribosome profiling experiments from recent studies associated with our laboratory, including but not limited to: Iwasaki et al [10], Werner et al [11], and Ishikawa et al [12]. In essence, the procedure is similar to that described in Ingolia et al (2012) [13]: cells are rapidly harvested and lysed under conditions that are expected to preserve in vivo ribosome positioning.…”
Section: Introductionmentioning
confidence: 99%
“…It has been the basis of ribosome profiling experiments from recent studies associated with our laboratory, including but not limited to: Iwasaki et al [10], Werner et al [11], and Ishikawa et al [12]. In essence, the procedure is similar to that described in Ingolia et al (2012) [13]: cells are rapidly harvested and lysed under conditions that are expected to preserve in vivo ribosome positioning.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the majority of changes in gene copy number will propagate to changes in the corresponding protein levels (Dephoure et al, 2014;Pavelka et al, 2010;Stingele et al, 2012) . However, models of aneuploidy of different species and analysis of gene copy number variation (CNV) in cancer have shown that CNVs of protein coding genes belonging to protein complexes tend to be attenuated at protein level (Dephoure et al, 2014;Gonçalves et al, 2017;Ishikawa, Makanae, Iwasaki, Ingolia, & Moriya, 2017) . In addition we have shown that some complex members can act as rate-limiting subunits and indirectly control the degradation level of attenuated complex members .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, gene dosage compensation was mostly reported at the protein level and not at the transcriptional level, whereby the stoichiometry of protein complexes in aneuploid cells determines that excess subunits are either degraded or aggregated to achieve dosage compensation (Brennan et al, 2019) . Another work, using the genetic tug-of-war technique showed that approximately 10% of the genome shows gene dosage compensation at the protein level (Ishikawa et al, 2017), although this approach was not designed to distinguished compensation at the transcriptional level. To our knowledge, the only previous evidence of gene dosage compensation at the transcriptional level in cancer cells was provided for some few genes by a report of the insertion of an additional chromosome 5 (Stingele et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The multiple consequences of aneuploidy are mainly regulated at the protein level due to a side-effect of protein folding defects and increased protein degradation by proteosome and autophagy (Donnelly & Storchová, 2014). An approach to identify genes with dosage compensation by increasing the copy number of individual genes using the genetic tug-of-war technique showed that approximately 10% of the genome shows gene dosage compensation, and consists predominantly of subunits of multi-protein complexes, which are regulated in a stoichiometry-dependent manner (Ishikawa, Makanae, Iwasaki, Ingolia, & Moriya, 2017), although this approach was designed to identify compensated genes at the protein level only.…”
Section: Introductionmentioning
confidence: 99%